The effects of upper limb, trunk, and pelvis movements on Apkubi Momtong Baro Jireugi velocity in taekwondo - Hoo, S.-H. (Korean Journal of Sport Biomechanics, 2016)
Objective: The purpose of this study was to investigate effects of upper limb, trunk, and pelvis kinematic variables on the velocity of Apkubi Momtong Baro Jireugi in Taekwondo. Method: Twenty Taekwondo Poomsae athletes (age: 20.8±2.2 years, height: 171.5±7.0 cm, body weight: 66.2 ±8.0 kg) participated in this study. The variables were upper limb velocity and acceleration; trunk angle, angular velocity, and angular acceleration; pelvis angle, angular velocity, and angular acceleration; and waist angle, angular velocity, and angular acceleration. Pearson's correlation coefficient was calculated for Jireugi velocity and kinematic variables; multiple regression analysis was performed to investigate influence on Jireugi velocity. Results: Angular trunk acceleration and linear upper arm punching acceleration had significant effects on Jireugi velocity (p<.05). Conclusion: We affirmed that angular trunk acceleration and linear upper arm punching acceleration increase the Jireugi velocity.